Impact of Mechanical Transplanting on Rice Productivity and Profitability- Review - Saha, Rajesh; Patra, Partha Sarathi; Ahmed, Arju Sahid (International Journal of Economic Plants, 2021)
Conventional rice transplanting methods are laboured exhaustiveand involves drudgery. On an average only transplanting operation takes one fourth of the total labour requirement of rice production under traditional system. Shifting of agricultural labourer towards urban areas for better remuneration creates labour shortage during peak time of transplanting. Lower plant density compared to desirable level under traditional transplanting method habitually farmers force to apply higher amounts of agro-input to compensate as result cost of cultivation has increased considerably and eventually get lesser grain yield. Under such circumstances, a cheap and labour redeemable way of rice transplanting without compromising grain yield is the need of the time. The mechanical rice transplanting is an alternative and encouraging choice for ensuring timely transplanting and also contributes to higher grain yield. Mechanical transplanting of rice is profitable over traditional methods and easy to operate. In spite of having superiority over the conventional transplanting, acceptance in the field level is stumpy due to high preliminary investment and dearth of awareness in growing mat type nursery. Divulging technical skill, confirming timely accessibility and boosting custom hiring may be some of the practical solutions for increasing the adoption rate of mechanical transplanting among farmers. This review focused on the positive and negative impact of mechanical transplanting on productivity and profitability of rice production.